In Your Eyes I See My Words : Homilies and Speeches from Buenos Aires, Volume 2: 2005-2008. - Francis, Pope (Fordham University Press, 2020)
In Your Eyes I See My Words, Volume 2 contains Pope Francis's homilies and speeches spanning from 2005 to 2008. Continuing what began in the first volume of this three-volume publication, Volume 2 shows Archbishop Bergoglio's growth as a pastor and a theologian/scholar in the midst of his people. At the same time, it shows him emerging as an international voice calling for changes in the way the Church carries out its ministry and its educational task on behalf of children, youth, adults, and church ministers. In his homilies from Christmas, Easter, and especially in his response to the tragic fire and deaths of 194 people at the nightclub Republica Cromañon, we see Bergoglio speak passionately to his parishioners, challenging them with equal portions of tenderness and righteous anger. Perhaps uniquely, we also watch as his audiences, prominence, and influence grow globally, foreshadowing who he will become in 2013 when he is elected Pope. On the larger national and international scale, Bergoglio addresses various conferences, such as the Argentina Press Association and the Episcopal Conference of Argentina of which he was elected President in 2005 and served the maximum possible term of six years. We see and read as his work takes him outside his country to Rome (2007) at the Pontifical Commission for Latin America; to Brasil (2007), where his presentation on the Crisis of Civilization and Culture at the Fifth CELAM Conference ends up shaping much of the Aparecida Conclusions; and finally, to Quebec (2008) as he speaks at the Forty-Ninth International Eucharistic Congress. All told, In Your Eyes I See My Words, Volume 2 is a glimpse into a period of time in which Archbishop Bergoglio grows immensely in thought, reflection, and action, laying the groundwork for the mature, thoughtful, and beloved Pope Francis he has come to be known as around the world.